Comparing feces collection methods for evaluating the apparent digestibility coefficient of brewers’ spent yeast in juvenile Atlantic salmon (Salmo salar) - Orellana, Paola; Márquez, Lorenzo; Ortloff, Alexander; Ruiz, Joceline; Dantagnan, Patricio; Hernández, Adrián J. (Frontiers in Veterinary Science, 2024)
Brewer's spent yeast (BSY), derived from Saccharomyces cerevisiae used in beer production, is a valuable protein source for aquafeeds. Estimations of apparent digestibility coefficients (ADC) for nutrients in BSY are crucial for its inclusion in aquafeeds. ADC estimations for Saccharomyces cerevisiae protein in rainbow are hardly comparable from a methodological point of view, whereas the ADC estimations for BSY protein in Atlantic salmon are only based on stripped feces, which are known to produce underestimations. Therefore, new determinations of ADC of BSY nutrients are necessary for the inclusion of this ingredient in practical diets for salmonids. This study is focused on determining unbiased ADC values for protein and energy from BSY in juvenile Salmo salar. To reduce systematic biases, fecal samples were collected using stripping and decantation methods, which are known to produce under-and overestimations, respectively. 780 fish (25.16 ± 4.88 g) were stocked in six tanks. A reference diet (50% protein, 20% lipid, 1% Cr2O3) was provided to three tanks, and a test diet (70:30 reference diet to BSY) to the other three. ADC for BSY protein was 84.70 ± 1.04% (decantation) and 70.50 ± 4.03% (stripping). For gross energy, stripped feces yielded an ADC of 52.04 ± 5.30%, while decantation resulted in 63.80 ± 1.17%. Thus, ADC estimates were taken as the average of the stripping-value and the decantation-value, resulting in 77.6% for BSY crude protein, which is appreciably higher than previously measured values in S. salar fed undisrupted S. cerevisiae, and in 57.9% for gross energy.